Digital technologies improving safety in the construction industry - Yi, W.; Wu, Peng; Wang, Xiangyu; Chan, A. (Routledge, 2018)
© 2018 selection and editorial matter, Adriana X. Sanchez, Keith D. Hampson and Geoffrey London; individual chapters, the contributors. In recent years, safety culture has emerged as one of the most important concepts in the construction industry (Biggs et al., 2005; Dingsdag et al., 2006; Fang et al., 2006). Fang et al. (2001) argued that decentralisation and mobility are two important factors leading to poor safety performance of the construction industry. Decentralisation refers here to the individual decisions that employees have to make when facing specific safety problems. Mobility implies that employees in the construction industry move among companies, sites and positions more frequently than those in other traditional industries (Fang et al., 2001). In the United States (US), the occupational fatality rate in construction ranks fourth after agriculture, mining and transportation; the construction industry has by far the largest number of fatal injuries (BLS, 2008). According to the Centre for Construction Research and Training, the construction safety and health research and training arm of North America's Building Trades Unions, there were at least 396 construction fatalities during 2005 as a result of falls. It is also reported that, in 2005, there were 36,360 non-fatal injuries resulting from falls, accounting for 23 per cent of the cases with days away from work in the construction industry (Centre for Construction Research and Training, 2007). In 2003, the fatal injury incidence rate in the United Kingdom (UK) was 4.0 per 100,000 construction workers. When collated with fatalities in all industries, construction accounted for 31 per cent of all work-related deaths in 2002-2003 (Haslam et al., 2005). Similar patterns are also found in Singapore. According to Ling et al. (2009), the fatality rate for the construction sector in Singapore was ‘unacceptably high’. In 2006, this rate was 9.4 per 100,000 persons employed and represented 39 per cent of the total workplace fatalities across all industries (Ministry of Manpower, 2006).